Lead-free BaTiO3 Nanowire Arrays-based Piezoelectric Energy Harvester. (24th April 2017) - Baek, Changyeon; Park, Hyeonbin; Yun, Jong Hyuk; Kim, Do Kyung; Park, Kwi-Il
ABSTRACT: Vertically aligned BaTiO3 nanowire (NW) arrays on a Ti substrate were adopted for use in piezoelectric energy harvesting device that scavenges electricity from mechanical energy. BaTiO3 NWs were simultaneously grown at the top and bottom surfaces of a Ti substrate by two-step hydrothermal process. To characterized the piezoelectric output performance of the individual NW, we transferred a BaTiO3 single NW that was selected from well-aligned NW arrays onto a flexible substrate and measured the electric signals during the bending/unbending motions. For fabricating a piezoelectric energy harvester (PEH), both NW arrays were sandwiched between two transparent indium tin oxide (ITO)-coated polyethylene terephthalate (PET) plastic films and then packaged with polydimethylsiloxane (PDMS) elastomer. A lead-free BaTiO3 NW array-based PEH produced an output voltage of about 90 V and a maximum current of 1.2 μA under periodically bending motions.